Measurement uncertainty on the circular features in coordinate measurement system based on the error ellipse and Monte Carlo methods. (2nd November 2016) - Du, Zhengchun; Zhu, Mengrui; Wu, Zhaoyong; Yang, Jianguo
Abstract: The uncertainty determination of the geometrical feature measurement for coordinate measuring machines (CMMs) is an essential part in the reliable quality control process. However, the most commonly-used methods for uncertainty assessment are difficult and require not only a large number of repeated measurements but also rich operation experience. Based on the error ellipse theory and the Monte Carlo simulation method, an uncertainty evaluation method for CMM measurements is presented. For circular features, the uncertainty evaluation model was established and extended into the use of an application of two holes' central distance measurement through Monte Carlo Simulation. The verification experiment of the new method was conducted and results were compared with the traditional ones and they fit reasonably well, which proved the validity of the proposed method.